(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Vascular endothelial growth factor (VEGF) is an essential factor for angiogenesis and plays important role in placental development. Objective: To investigate the association between VEGF single nucleotide polymorphisms (SNPs) +936 Cytosine/Thymine (C/T) and -634 Guanine/Cytosine (G/C) and preeclampsia risk. Methods: A total of 50 cases of pregnant women with preeclampsia and 50 healthy pregnant women (as a control) were involved in this case control study. Blood samples were collected form each woman and the Deoxyribonucleic acid (DNA) was extracted. Amplification of VEGF gene was done by conventional polymerase chain reaction (PCR) and then detection of SNPs-634 G/C and +936 C/T were carried out by restriction fragment length polymorphism PCR (PCR-RFLP). Results: The frequency of different genotypes of VEGF SNPs +936 C/T &-634 G/C are in accordance with Hardy Weinberg equilibrium. VEGF polymorphism +936 C/T appeared in 3 genotypes after digestion with restriction enzymes Cytosine Cytosine (CC), Cytosine Thymine (C/T) & Thymine Thymine (TT). VEGF SNP -634 G/C appeared in 3 genotypes after digestion with restriction enzymes; those were Guanine Guanine (GG), Guanine Cytosine (GC) and CC. The heterozygous genotype CT of polymorphism +936 C/T was more frequent among preeclamptic patients than the controls (26% versus 16%). Likewise, TT genotype was more frequent among preeclamptic patients (8% versus 2%) with no significant differences. At the allelic level, the difference was more prominent. The frequency of mutant allele (T allele) was much more frequent in preeclamptic patients than controls (21% versus 10%) with a statistically significant difference (p=0.049). Although CC genotype of polymorphism -634 G/C was more frequent among preeclamptic patients than controls (14% versus 10%), the difference was not significant (p=0.704). Likewise, there were no significant differences in allele frequency. Conclusion: The study suggested that the mutant T allele of VEGF +936 C/T polymorphism was associated with increased preeclampsia risk and disease development. Keywords: Vascular endothelial growth factor, polymorphisms, preeclampsia Citation: Khaleel MF, Al-Moayad HA. Association between vascular endothelial growth factor gene polymorphisms and the risk of preeclampsia in Iraqi pregnant women. Iraqi JMS. 2022; 20(1): 106-112. doi: 10.22578/IJMS.20.1.14